A educação em direitos humanos nos manuais do professor da coleção didática projeto buriti - história (PNLD/2013): os direitos das crianças e a formação do professor em foco - Carvalho, Emilene Julia da Silva Freitas (2017)
This master's research refers to the presence of Human Rights Education (EDH) in the Teachers Manuals (EDH) of Didactic Books (MP) of History, distributed by the National Program of Didactic Books - PNLD in early years, in 2013, and its relation with the conceptions on Human Rights (DH) and human dignity through the rights of children established in the Statute of the Child and Adolescent (ECA). The research assumed that there are different conceptions about human rights (universalist, cultural relativist and intercultural) and tried to understand which of them permeated the Teacher Manuals of the didactic collection Buriti Project: History approved in PNLD 2013 and how it contributes to the formation of teachers in EDH based on the rights of the children that are foreseen in the ECA. As an object of analysis, we chose the MP of this collection, since this was the most adopted among the thirty-five works approved and distributed in brazilian public schools in the year of 2013. The research methodology used was the qualitative investigation through the discursive textual analysis. The analyzes pointed out that the didactic collection Buriti Project: History did not specifically insert the theme of EDH in the MP, but themes that relate to children's rights in the texts, images and activities of the section "The world we want" and the topic "Education in Values", addressing them mainly through the universalist conception of Human Rights. This collection contributes little to the formation of the teacher for the EDH, since it guides him on how to develop the activities of the book based on this conception, as if it were the only one existing, without contextualizing the selection and approach of the contents related to DH and ECA.